Enactive cooperative actions in management - Machado, César Costa (2021)
From the conversations with teachers, administrative employees, and pedagogical managers of a Federal Institute of Education that in their professional constitution had prioritized the technical formation we approached, in this study, the cooperative actions that can contribute to the action of participative management. We problematize three cognitive domains of the educational manager, which are: professional, political, and epistemological. The dialogues were established by open and semi-structured interviews as they were transcribed and analyzed through the Collective Subject Discourse methodology that enables the construction of speech-síntheses that represent the similar thought of a collectivity. During the research, it is possible to observe that the constitution of a teacher in the position of a manager resembles an employer, his activities based on the resolution of short-term demands distracted isolate him from the administrative actions congruent to the current procedures that teaching with digital technologies requires. In the end, we show that the integration of administrative and pedagogical collectives into decisions and conflict resolution to increase efficiency reduces the isolation between departments and prevents adversities from being located only in one area, democratizing problems and solutions.